Relationship between bedtime, nighttime sleep duration, and anxiety symptoms in preschoolers in China - Qiu, Shuang-Yan; Yin, Xiao-Na; Yang, Yanni; Li, Ting; Lu, Dali; Li, Jie-Min; Yang, Wei-Kang; Wen, Guo-Ming; Zhang, Jing-Yu; Zhang, Yan; Lei, Hai-Yan; Wang, Xin; et al. (Frontiers in Psychology, 2024)
Background Sleep problems in preschoolers are becoming increasingly prominent, and the association between sleep status and anxiety symptoms has attracted growing attention. However, studies investigating the relationship between bedtime and nighttime sleep duration in preschoolers and their anxiety symptoms remain scant. We used the large sample data from the Longhua Cohort Study of Children in Shenzhen, China (LCCS) to analyze the association between bedtime and sleep in preschoolers and their anxiety symptoms. Methods A cross-sectional study of 69,138 preschoolers in Longhua District, Shenzhen, China was conducted in 2022. Data on sociodemographic characteristics of families, bedtime, nighttime sleep duration of preschoolers, and their anxiety symptoms (measured by the Spence Preschool Children Anxiety Scale) were collected through a structured questionnaire completed by the parents. Using binary logistic regression models, the relationship between bedtime, nighttime sleep duration, and childhood anxiety symptoms was examined. Results The bedtimes of preschoolers were concentrated between 21:01–22:00 (52.41%). Among the preschoolers, 38.70% had bedtimes later than 22:00, and 75.49% had insufficient nighttime sleep duration. The positive screening rate for anxiety symptoms among preschoolers was 3.50%. After adjusting for confounding factors using binary logistic regression models, compared with preschoolers with bedtime ≤21:00, The OR (95%CI) values of anxiety in preschoolers with bedtime ≥23:01, 22:01–23:00 and 21:01–22:00 were 2.86 (2.21–3.69), 1.51 (1.27–1.79) and 1.48 (1.26–1.76), respectively. Compared with those with sufficient nighttime sleep duration, the OR (95%CI) of children with nighttime sleep duration less than 9 h was 1.36 (1.23–1.51). Conclusion An association exists between bedtime and nighttime sleep duration in preschoolers and their anxiety symptoms. Preschoolers with 21:00 for bedtime and a nighttime sleep duration of 10 h may have lower anxiety symptoms. These findings support the importance of adequate sleep for preventing anxiety symptoms in children.